The Etiology of Non-cirrhotic Portal Hypertension. A Study of 105 Consecutive Patients - Muti, Leon Adrian; Sparchez, Zeno; Iobagiu, Silviu; Acalovschi, Monica (Medicine and Pharmacy Reports, 2014)
Background and aims. Non-cirrhotic portal hypertension (NCPHT) represents an entity that is still incompletely studied as a whole. The aim of the present study is to obtain information on the prevalence, etiology, clinical and biological features of the NCPHT. Methods. This is a prospective cross-sectional study of a population of 105 consecutive patients with NCPHT admitted in the Third Medical Clinic in Cluj-Napoca, Romania from October 2004 to October 2006. As control group, 105 consecutive cirrhotic patients admitted in the same clinic from September 2006 to October 2006 were studied. In this two-year period a total of 1474 patients with portal hypertension (PHT) were admitted. Results. Non-cirrhotic PHT was present in 105/1474 (7.12%) of the patients with PHT. Solid cancers had represented the dominant etiology of PHT (58%). Venous thrombosis (35.2%), extrinsic compression (31.4%) and vascular tumor invasion (28.5%) were almost equally responsible for the NCPHT. Prehepatic PHT was dominant (83.8%) and 33.3% of the patients had segmental PHT in the NCPHT group. The gastric varices (12/69 patients v. 0/100 patients) and the associated esophageal + gastric varices (10/69 patients v. 5/100 patients) were significant more frequent in NCPHT than in cirrhosis (p<0.05). The mean value of platelet count (249,904±13,281/mm 3 ) was normal in the NCPHT group while in the cirrhotic group thrombocytopenia (108,215±65,069/mm 3 ) was noticed. A significant difference was found between the platelet count in NCPHT group and cirrhosis group in patients with spleen diameter over 120 mm (243,240±126,328 v. 106,175±66,470) (p<0.001) as well as a diameter less than 120 mm (214,333±75,191 v. 128,306±54,663) (p<0.001). A negative correlation was found between the platelets count and spleen size in the cirrhosis group (r=-0.292; p=0.002), but not in the NCPHT group (r=0.016; p=0.871). Conclusion. Patients with NCPHT represented 7.12% from the patients with PHT. Thrombosis, tumor invasion and extrinsic compression were equally responsible for the NCPHT. One third of the patients with PHT had segmental PHT. The patients with NCPHT had normal platelets value. In contrast, thrombocytopenia was found in those with cirrhosis, which was negatively correlated with spleen size (might not be caused by PHT but by advanced hepatic fibrosis).